Laser Driven Electron‐Positron Pair Creation–Kinetic Theory Versus Analytical Approximations. Issue 10 (December 2013) - Smolyansky, S. A.; Bonitz, M.; Prozorkevich, A. V.
Abstract The dynamical Schwinger effect of vacuum pair creation driven by an intense external laser pulse is studied on the basis of quantum kinetic theory. The numerical solutions of these kinetic equations exhibit a complex time dependence which makes an analysis of the physical processes difficult. In particular, the question of secondary effects, such as creation of secondary annihilation photons from the focus spot of the colliding laser beams, remains an important open problem. In the present work we, therefore, develop a perturbation theory which is able to capture the dominant time dependence of the produced electron‐positron pair density. The theory shows excellent agreement with the exact kinetic results during the laser pulse, but fails to reproduce the residual pair density remaining in the system after termination of the pulse. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)